Hydrops Fetalis - Azmi, Jofril; Sriyanti, Roza (Andalas Obstetrics And Gynecology Journal, 2019)
Objective: To report cases of hydrops fetalisMethod: Case reportResults: The case was a female patient aged 36 years, with a diagnosis of G3P1A1H1 gravid 23-24 weeks + Hydrops Fetalis + 1x SC former. On ultrasound examination at 23-24 weeks of age, fetal biometry was found; BPD: 58.9 mm, HC: 211.0 mm, AC: 202.5 mm, FL: 44.4 mm, HL: 40.7 mm, EFW: 417 gr, SDP: 12.79 cm, FHR: 162x / minute, shows anasarcoma edema (+), hydrothoric (+), ascites (+), impression: gravid 23-24 weeks according to biometry, live fetus, Hydrops fetalis, polyhydramnios. Then amniocentesis was carried out followed by a chromosome analysis examination carried out by the G-Banding technique. The chromosomes from 18 cells from 3 different cell culture preparations were carried out and obtained the number of chromosomes in each cell studied was 46, XY, which means that the number of chromosomes is 46. fruit with the fetal sex chromosome is XY. No major structural abnormalities were seen. At 25-26 weeks of gestation, the baby was born by SC with BBL: 2100 gr, PB: 32 cm, maceration degrees 2- 3, Hydrops Fetalis.Conclusion: Hydrops Fetalis is an abnormal accumulation of fluid in 2 or more compartments of the fetal body. The prenatal diagnosis of Hydrops Fetalis can be confirmed by fetal imaging, maternal hematology, amniocentesis.Keywords: Hydrops Fetalis, polyhydramnios